Dreams Deferred: The Impact of Legal Reforms on Undocumented Latino Youth. (December 2014) - Martinez, Lisa M.
Deferred Action for Childhood Arrivals was enacted in August 2012, allowing undocumented youth who meet eligibility criteria to live and work in the United States for a period of 2 years. In April 2013, the Governor of Colorado signed the Advancing Students for a Stronger Economy Tomorrow bill granting undocumented students reduced tuition in the state's public universities. In the absence of comprehensive immigration reform, this article addresses how legal reforms affect undocumented Latina/o youth in the context of a shifting political landscape in Colorado. Specifically, I address how these reforms affect immigrant youths' access to higher education and employment opportunities. Data from qualitative interviews with 18 Latina/o undocumented youth ages 16 to 25 show that, while immigration reforms have created some opportunities, the policies' limitations leave immigrant youth in "holding patterns" that delay or impede their access to higher education and, consequently, upward mobility. I also shed light on their perceptions of these reforms.